Cultural Symbolism: Thai Food Products in the United States Markets - Watanasin, R.; Whiteley, Alma (ICMS, 2012)
This research, aimed to understand the meanings of Thai food products, and associated cultural symbolism, in the United States. A qualitative study spanned Thailand and several cities in the United States. Interviews were conducted and symbolic materials presented. Results showed that there is a strong American food culture and are diverse consumers. Thai food is accepted but as an ethnic (non American) choice, which paradoxically appeals to authentic food culture, but is also ‘americanised’. Recognition of local (Thai) symbols were recognised, but not associated with product standards. Theoretically, acculturation in a host culture occurs more easily in food consumption. Findings reveal that food acculturation is multidirectional, whereby many ethnic cuisines are mixed together. As evidenced by an increasing number of restaurants serving fusion or adaptation of ethnic (including Thai) food, the notion of ‘one food reflects one culture’ is too simplistic.